Analisis Perbandingan Studi Kelayakan Budidaya Jamur Tiram dengan Pendekatan Model Outsourcing di Kota Metro - Yateno Yateno; Ratmono Ratmono (Akuisisi: Jurnal Akuntansi, 2014)
The high market prospects will stimulate farmers Oyster Mushrooms in Metro City. Currently businesses oyster mushrooms in Sumber Sari, Bantul Metro and surrounding areas such as complex 16 C has been pretty much a glance at the Mushroom cultivation. The feasibility study on a regular basis requires a source of capital for investment is quite large compared with the Outsourcing Model approach, but retrofitting Model Outsourcing requires a fairly large variable costs compared to regular cultivation, all of these approaches are accepted and feasible. Based on the financial aspect, that the oyster mushroom business capacity of 10,000 baglog per kumbung size 7 feet x 9 feet is able to produce fresh oyster mushrooms 3,600 kg per period (4 months) or 7,200 kg per year, test results analisisi financial aspects such as PV (present value) net cash, the NPV (net Present Value), PP (Payback Period), PI (Propfitabilitas Index), that the regular cultivation method is more efficient, precise and more profitable than the Outsourcing Model approach.Key words: Outsourcing Model Approach, financial feasibility.